The Association Between Knowledge of Hypertension and Compliance with Antihypertensive Medication on Prospective Hajj Pilgrims - Riskiyah Riskiyah; Ermin Rachmawati; Amalia Nur Aisa (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Indonesia is the most significant contributor to Hajj pilgrims, with health risks that are still relatively high, one of which is Hypertension. Lack of knowledge about Hypertension is an obstacle to controlling Hypertension. In addition, half of hypertension-related deaths could be prevented by compliance with taking antihypertensive medication. Objective: This study sought to determine the association between prospective Hajj pilgrims' compliance with medication and their knowledge of hypertension in 2023 who suffer from Hypertension in Batu City. Method: The research used quantitative methods with a cross-sectional design. The sample for this research was 39 Prospective Hajj pilgrims, and total sampling was taken. Result: The results of the study on Prospective Hajj pilgrims who suffer from Hypertension in Batu City showed that the majority of their knowledge about Hypertension was in a good category, 23 people (59.0%), the level of compliance with taking medication was in the low sort 24 people (61.5%); There was no correlation between medication adherence and knowledge of hypertension (p-value 0.185). Conclusion: Non-compliance with taking medication prospective Hajj pilgrims in Batu City can be changed by regularly providing education about the importance of taking medication and the risks that can arise if they do not regularly take hypertension medication